2009
DOI: 10.1002/dvg.20485
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genes that interact with Drosophila presenilin and amyloid precursor protein

Abstract: The gamma-secretase complex is involved in cleaving transmembrane proteins such as Notch and one of the genes targeted in Alzheimer's disease known as amyloid precursor protein (APP). Presenilins function within the catalytic core of gamma-secretase, and mutated forms of presenilins were identified as causative factors in familial Alzheimer's disease. Recent studies show that in addition to Notch and APP, numerous signal transduction pathways are modulated by presenilins, including intracellular calcium signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 151 publications
(133 reference statements)
1
33
0
Order By: Relevance
“…Our findings therefore implicate PS in the expression or stability of CCS by a mechanism that is still uncertain. This may reflect a functional, two-way interaction because a recent screen to identify genes that interact with Drosophila presenilin (Psn) identified CCS via its ability to suppress a Psnmediated dominant negative phenotype (42). In light of our findings, it is notable that BACE1 binds Cu ϩ and interacts with CCS, and BACE1 expression reduces the activity of SOD1 (43).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our findings therefore implicate PS in the expression or stability of CCS by a mechanism that is still uncertain. This may reflect a functional, two-way interaction because a recent screen to identify genes that interact with Drosophila presenilin (Psn) identified CCS via its ability to suppress a Psnmediated dominant negative phenotype (42). In light of our findings, it is notable that BACE1 binds Cu ϩ and interacts with CCS, and BACE1 expression reduces the activity of SOD1 (43).…”
Section: Discussionmentioning
confidence: 66%
“…Although many aspects of the uptake process remain uncertain, evidence suggests that both Cu 2ϩ and Zn 2ϩ enter cells by binding to copper transporter 1 or a ZIP on the surface and are then ferried within an endosome. Notably, like CCS, ZIP1 also rescued the dominant negative Psn phenotype in Drosophila (42). We hypothesize that PS is involved in handling this metal intake endosome through autophagic pathways that have recently come to light (52).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Notably, 58 modifiers interacted with АРР, including those involved in calcium signaling. These results provide strong evidence for a link between presenilins, APP, and calcium homeostasis, and suggest that these may play an important role in AD pathogenesis [van de Hoef et al, 2009].…”
Section: Screening For Genetic Modifiersmentioning
confidence: 61%
“…Further, many of the known -secretase targets and pathways are also conserved, making Drosophila a useful model with which to identify novel PSN interactors and regulatory mechanisms. We previously carried out a screen for modifiers of Drosophila Presenilin (Psn) and APP (van de Hoef et al, 2009) and found that mutations in FKBP14 could suppress the phenotype associated with overexpression of Psn (van de Hoef et al, 2009).…”
Section: Introductionmentioning
confidence: 99%